Population aggregates from administrative data samples-how good are they? - Philipp vom Berge (Journal for Labour Market Research, 2023)
Researchers regularly use administrative micro-data samples to approximate subgroup aggregates from the full population. In this paper, I argue that the most commonly used method to do this is often not optimal. I outline some alternatives and compare their relative performance in selected cases. I also discuss the effect of statistical disclosure control on the aggregated data and how researchers can reduce bias resulting from censoring.
Keywords: C43; C80; 330; SIAB; BHP; Microdata; Aggregation; Statistical Disclosure Control